Розроблення способу отримання фруктово-желейного мармеладу оздоровчого призначення - Башта (Шеремет), Алла Олексіївна; Лещинська, Тетяна Сергіївна (My University, 2013)
У статті викладено результати досліджень ревеню, бузини та водно- спиртових екстрактів трави чебрецю, фіалки, материнки на вміст фенольних сполук й органічних кислот. Оцінено органолептичні та якісні показники готового продукту, доведено ефект збагачення мармеладу катехінами, флавонолами, антоціанами за рахунок використання збагачувачів. Кінцевим результатом запропонованого дослідження є створення фруктово-желейного мармеладу оздоровчого призначення. This work is devoted to development of a process for obtaining the fruit and jelly marmalade with pectin as structurant, gelling apple and rhubarb sauce enriched by fruit juice and black elderberry and extracts of herbs (thyme, oregano and violet). The choice of this raw material is due to the fact that vegetable raw material is a valuable source of biologically active substances, the content of which in traditional marmalade is negligible. Apolimeric forms of plant enriched with flavonoids can depress radical reactions of the organism and they can be combined in a best way with carbohydrate foods. Simple sugars enter the bloodstream immediately bringing antioxidants of herbal raw material. Choice of phytoadditives and directions of their useage based on disease frequency and requirements developed by nutritionists and pediatricians are outlined in this article. The paper presents the results of investigation of rhubarb, elderberry and water-alcohol extracts of herbs thyme, violets, marjoram for the content of organic acids, phenolic compounds and assesses organoleptic and quality of the finished product; the enrichment effect of marmalade catechins, flavonols, anthocyanins has been identified.
Keywords: мармелад; пюре ревеню; сік плодів бузини; екстракт материнки звичайної та фіалки триколірної; rhubarb puree; marmalade; elderberry juice; extract oregano and viola; tricolor; кафедра технології оздоровчих продуктів